Implementation of Bank Indonesia CSR Program on Empowerment the Micro, Small, Medium Enterprises (MSMEs) (Study at the Artisans of Tenun Ikat Bandar Kidul, Kediri City, East Java) - Purwaning Diah, Martina (Jurnal Ilmiah Administrasi Publik, 2016)
Kediri City is famous with product of â€œTahu Kuning&Takwaâ€. But, Kediri Cityhas other potential that can be developed to encourage the local economicdevelopment is Woven Home Industry Tenun Ikat. Nowadayas, the existence of Tenun Ikat Bandar Kidul product was less unknown in the market. It encourages Bank Indonesia to take a part on empowerment them to be survive in competition era. This research aimed to analyze the implementation of Bank Indonesia CSR Program to empower the artisans. The result revealed that the commitment, communication, and support among stakeholders such as: Bank Indonesia, Local Government and artisans were not good enough to success the CSR program from Bank Indonesia.